Modelo geológico del yacimiento “viche conguime 3” para la determinación de su valor económico - Cires Morán, José Antonio (2009)
The “Viche Conguime 3” deposit has been explored and studied by several mining companies since the decade of 1970s, many positive results have been generated, such as in geochemistry of sediments and rocks, and also diamond drilling. Since this deposit has been explored in many times, therefore with different methods and objectives, a large amount of field data have been created: lithology, alteration, mineralization and structural maps; it is necessary to compile all this data, digitize it when needed and combine everything into a single database, load it into a Geographic Information System, so it can be useful in the definition of a drilling program, geological modeling and further economic evaluation of the deposit.